Comparison of Neuroprotective and Cognition-Enhancing Properties of Hydrolysates from Soybean, Walnut, and Peanut Protein. (25th July 2016) - Li, Wenzhi; Zhao, Tiantian; Zhang, Jianan; Wu, Changping; Zhao, Mouming; Su, Guowan
Abstract : Hydrolysates were prepared from soybean, walnut, and peanut protein by papain, respectively. Their amino acid compositions and molecular weight distributions, the effects of various hydrolysates on H2 O2 -induced injury PC12 cells, and cognition of mice were investigated, respectively. Results showed that the three hydrolysates were dominated by the peptides with 1–3 KDa with large amount of neurotrophic amino acids. All the hydrolysates exhibited much stronger inhibitory activity against H2 O2 -induced toxicity than cerebrolysin, and soy protein hydrolysate showed the highest activity. Moreover, the hydrolysates also could reduce the rate of nonviable apoptotic cells at the concentration of 2 mg/mL. The test of animal's cognition indicated that three hydrolysates could present partly better effect of improving recurred memory ability of normal mice and consolidated memory ability of anisodine-treated mice than piracetam. Therefore, soybean, walnut, and peanut protein hydrolysates were recommended as a potential food raw material for prevention or treatment of neurodegenerative disorders.